1996
DOI: 10.1289/ehp.96104s5861
|View full text |Cite
|
Sign up to set email alerts
|

Breath measurements as volatile organic compound biomarkers.

Abstract: A brief review of the uses of breath analysis in studies of environmental exposure to volatile organic compounds (VOCs) is provided. The U.S. Environmental Protection Agency's large-scale Total Exposure Assessment Methodology Studies have measured concentrations of 32 target VOCs in the exhaled breath of about 800 residents of various U.S. cities. Since the previous 12-hr integrated personal air exposures to the same chemicals were also measured, the relation between exposure and body burden is illuminated. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 46 publications
4
51
1
Order By: Relevance
“…For example, while Egeghy et al (2000) found that benzene in personal air and exhaled breath were highly correlated (r ¼ 0.77 for the logged levels) following short (1-10 min) exposures at levels ranging from approximately 4 p.p.b. to 10 p.p.m., Wallace et al (1996) would not recommend exhaled breath as a surrogate for VOC exposure at levels less than 1 p.p.m. (Wallace et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while Egeghy et al (2000) found that benzene in personal air and exhaled breath were highly correlated (r ¼ 0.77 for the logged levels) following short (1-10 min) exposures at levels ranging from approximately 4 p.p.b. to 10 p.p.m., Wallace et al (1996) would not recommend exhaled breath as a surrogate for VOC exposure at levels less than 1 p.p.m. (Wallace et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…to 10 p.p.m., Wallace et al (1996) would not recommend exhaled breath as a surrogate for VOC exposure at levels less than 1 p.p.m. (Wallace et al, 1996). Similarly, our previous study of benzene biomarkers found that albumin adducts of some reactive benzene metabolites, namely, benzene oxide and 1,4-benzoquinone, were clearly related to occupational benzene exposures above 1 p.p.m.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using breath tests to evaluate exposure to ETS is very promising given that it is a procedure that is safe and easy to perform. Preliminary studies have suggested that some VOCs detected in breath samples may be biomarkers (e.g., 1,3-butadiene, benzene, 2,5-dimethylfuran) [8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…Several urinary metabolite assays are available but these methods generally lack sensitivity and/or specificity when applied to environmental exposures. However, breath sampling of VOCs is a valid method for evaluating environmental exposure (32,33). This methodology is especially well suited for children because of its noninvasiveness and ease with which samples can be collected.…”
Section: Application Of Biomarker Study Designs For Childrenmentioning
confidence: 99%